Pengaruh Dosis Alam Terhadap Persepsi Nilai dan Loyalitas Pelanggan Kedai Kopi Era New Normal Live - Purwanto, Purwanto; Harahap, Dedy Ansari; Amanah, Dita; Gunarto, Muji; Umam, Khairul (Universitas muhammadiyah palembang, 2020)
This study aims to test the dose of nature (manicured gardens, fountains, and trendy entertainment) as a green design in the coffee shop on the perception of value that will ultimately determine the level of loyalty for customers in the direction of new normal life. Data were obtained from a sample of 500 respondents who visited coffee shops in Surabaya. By using AMOS 18.0, the following results were found, first, the green design significantly influenced the perception of utilitarian values, the second the green design significantly influenced the perception of hedonic values, the three utilitarian values significantly influenced loyalty and finally, hedonic values significantly affected loyalty on a coffee shop.